Easy American idioms : [hundreds of idiomatic expressions to give you an edge in English!] (New York : Living Language, 2006)
Offers twenty lessons designed to teach common American idiomatic expressions to foreign speakers and features simple definitions, examples, practice exercises, and natural dialogues.
Subtitle from container.
Intermediate ESL.
Accompanying book written by Rachel Varra ; edited by Christopher Warnasch.
Compact discs.
At head of title: Living Language.
Keywords: Americanisms; English language -- dioms. -- United States; English language -- Study and teaching; English language -- Sound recordings for foreign speakers